PENEGAKAN HUKUM TINDAK PIDANA PERJUDIAN TEBAK ANGKA DI WILAYAH HUKUM POLRES INDRAGIRI HULU BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA - Nainggolan, Awet Lestari; Harahap, Irawan; Kadaryanto, Bagio (The Juris, 2024)
Number guessing gambling in the jurisdiction of the Indragiri Hulu Police is a serious threat to public security and order. The social and economic impacts resulting from this gambling are disturbing the community and damaging family life. Reports from families and the community are important elements in taking action against gambling. The method used is sociological legal research. Based on the results of the study, it is known that law enforcement of the crime of number guessing gambling in the jurisdiction of the Indragiri Hulu Police based on the criminal code has not been running optimally, because there are still cases of number guessing gambling every year in the Indragiri Hulu Police. The police conducted raids and collected evidence supporting the crime of number guessing gambling. Obstacles in law enforcement of the crime of number guessing gambling in the jurisdiction of the Indragiri Hulu Police based on the criminal code are the lack of sufficient evidence due to the high level of confidentiality, limited resources available, and minimal reports from the public, because the public is often reluctant to report number guessing gambling for certain reasons, such as fear of revenge from the perpetrators or because they themselves are involved in the practice. Efforts to overcome obstacles in enforcing the criminal law on number guessing gambling in the jurisdiction of the Indragiri Hulu Police based on the criminal code are the use of more sophisticated technology and surveillance systems, the need to increase the capacity of law enforcement officers in terms of investigation and use of technology, law enforcement against perpetrators of number guessing gambling is carried out firmly and consistently without discrimination, and strengthening intelligence networks and closed investigations.